HUBUNGAN STATUS GIZI DAN TEKANAN DARAH DENGAN KADAR C-REACTIVE PROTEIN DARAH PADA SUBJEK DISLIPIDEMIA - Mira Dewi; Rimbawan Rimbawan; Agustino Agustino (Jurnal Gizi dan Pangan, 2013)
The objective of this study was to analyze the association of nutritional status (Body Mass Index, waist circumference, waist-hip ratio, and body fat mass) and blood pressure with inflammation status which was assessed by blood C-reactive protein level in dyslipidemic subjects. The study design was cross sectional survey involving 81 dyslipidemic subjects in Bogor. The study showed that there were significant correlations between BMI, waist-hip ratio, body fat mass, and diastolic blood pressure with blood CRP level (p<0.05). In conclusion, the higher percentage of over nutritional status, body fat mass, and diastolic blood pressure, the higher status of inflammation.Keywords: